2021
DOI: 10.1111/jgh.15431
|View full text |Cite
|
Sign up to set email alerts
|

Simple non‐invasive scoring systems and histological scores in predicting mortality in patients with non‐alcoholic fatty liver disease: A systematic review and meta‐analysis

Abstract: Background and Aim: There is debate among the hepatology community regarding the simple non-invasive scoring systems and histological scores (even it was developed for histological classification) in predicting clinical outcomes in patients with non-alcoholic fatty liver disease (NAFLD). This study aimed to determine whether the presence of simple non-invasive scoring systems and histological scores could predict all-cause mortality, liver-related mortality, and liver disease decompensation (liver failure, cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…A recent study based on a large European cohort of over 1100 patients reported NFS and FIB-4 were the best predictors of future LREs but had AUCs below 0.80 15 . Furthermore, a recent systematic review and meta-analysis confirmed the relatively poor performance of NFS and FIB-4 in the prediction of liver-related outcomes in patients with NAFLD and underscored the need for a more accurate model such as the NOS to assist clinicians in management decisions 52 . A recent study from Sweden has highlighted stratification by age, FIB-4, Gamma glutamyltransferase, and serum glucose aids identification of future risk of severe liver disease 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study based on a large European cohort of over 1100 patients reported NFS and FIB-4 were the best predictors of future LREs but had AUCs below 0.80 15 . Furthermore, a recent systematic review and meta-analysis confirmed the relatively poor performance of NFS and FIB-4 in the prediction of liver-related outcomes in patients with NAFLD and underscored the need for a more accurate model such as the NOS to assist clinicians in management decisions 52 . A recent study from Sweden has highlighted stratification by age, FIB-4, Gamma glutamyltransferase, and serum glucose aids identification of future risk of severe liver disease 53 .…”
Section: Discussionmentioning
confidence: 99%
“…[15] Furthermore, a recent systematic review and meta-analysis confirmed the relatively poor performance of NFS and FIB-4 in the prediction of liver-related outcomes in patients with NAFLD and underscored the need for a more accurate model such as the NOS to assist clinicians in management decisions. [52] A recent study from Sweden has highlighted stratification by age, FIB-4, Gamma glutamyltransferase, and serum glucose aids identification of future risk of severe liver disease. [53] Further comparison of the NOS with this method and other emerging fibrosis scores such as the NAFLD cirrhosis score is warranted to determine the optimal prognostic score.…”
Section: Discussionmentioning
confidence: 99%
“…However, liver biopsy as the gold standard is inappropriate to screen clinically significant fibrosis because of its features like invasive, inconvenient and expensive. Some studies have shown that conventional non-invasive scores, such as NFS 9 , FIB-4 10 , and APRI 11 , have prognostic significance of death for NAFLD patients [12][13][14] . However, their results were controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, their results were controversial. A meta-analysis including 19 longitudinal studies showed that only the NFS > 0.676 was predictive of overall mortality, while FIB-4 and APRI failed 14 . And a retrospective analysis including 646 NAFLD patients proven by liver biopsy revealed that although FIB-4 and NFS could precisely predict the risk of overall mortality of NAFLD patients, owing to the AUC values were not high enough (FIB-4, 0.72 [95% CI, 0.68-0.76]; NFS, 0.72 [95% CI, 0.68-0.76] and APRI, 0.52 [95% CI, 0.47-0.57]), so they were not useful in the clinical practice and new methods are needed to confirm the prognosis of NAFLD patients 13 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the diagnosis of MAFLD emphasizes a diagnosis based on three alternative methods, i.e., “detected either by blood biomarkers/scores, imaging techniques or by liver histology”. Therefore, serum- and image-based methods were recently proposed in multiple studies for the screening and diagnosis of mild/severe hepatic steatosis and NAFLD/MAFLD [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%